SUMBANGSIH PENDIDIKAN ISLAM DALAM PEMBENTUKAN GENERASI EKSISTENSIALIS (Rekonstruksi Pemikiran Mulla Sadra dan Jean P. Sartre) - Achmad Fawaid (Universitas Nurul Jadid, 2016)
This article is to examine the contribution of Islamic education in the production of existensialist generation, those who had self-consciousness in the primordial facticity in the unconsciousnessed world. By reconstruction of Muslim philosopher Mulla Sadra’s and existensialist philosopher Jean P. Sartre’s ideas, this study attempts to search for a shared point between both ideas and to create a new matrix on the existensialist generation. Finally, it is partly aimed to point out that Islamic education, which was commonly underestimated as having left hand, had important role to meet requirement in producing those who had ‘criterion’ of being existensialists.